Edukasi Perilaku Hidup Bersih dan Sehat Sebagai Strategi Peningkatan Sanitasi Lingkungan di Wilayah Pesisir - Endang Purnawati Rahayu; Budijono Budijono; Indra Suandy (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2025)
The implementation of clean and healthy living behaviors is still relatively low in coastal areas due to a lack of understanding and knowledge among the community about the importance of clean and healthy living behaviors and environmental sanitation conditions. The lack of adequate sanitation facilities will have a direct impact on the risk of environment-based diseases and reduce the quality of life of coastal communities. Therefore, this community service activity aims to provide education and guidance on clean and healthy living behaviors as an initial and strategic step in improving environmental sanitation in coastal areas. The community service method involves counseling and discussions with village officials and the community of Pasiran Village, Bantan District, Bengkalis Regency, and analysis using pre-test and post-test methods to measure the success of this community service activity. The results of the community service activity showed an increase in the understanding and knowledge of coastal communities regarding clean and healthy living behaviors. The pre-test and post-test results indicated an increase in knowledge from 65% to 90%, representing a 25% improvement. Additionally, this activity provided an overview of the environmental sanitation conditions in coastal areas, thereby benefiting the enhancement of coastal communities' knowledge about clean and healthy living behaviors. Furthermore, support from health centers through community health workers is needed to consistently provide information.